2019
DOI: 10.1016/j.jconrel.2019.06.035
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing treatment delivery and deposition in mouse lungs using in vivo x-ray imaging

Abstract: The complexity of lung diseases makes pre-clinical in vivo respiratory research in mouse lungs of great importance for a better understanding of physiology and therapeutic effects. Synchrotron-based imaging has been successfully applied to lung research studies, however longitudinal studies can be difficult to perform due to limited facility access. Laboratory-based x-ray sources, such as inverse Compton x-ray sources, remove this access limitation and open up new possibilities for pre-clinical small-animal lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 60 publications
0
31
0
Order By: Relevance
“…PB‐PCXI utilizes differences in X‐ray refractive index and associated phase shifts at air–tissue interfaces for enhancing soft tissue contrast (e.g., in the lung) as compared to X‐ray absorption . Building on our previously published in vivo PB‐PCXI studies in murine lungs, the present study demonstrates that combined in vivo PB‐PCXI and ex vivo fluorescence imaging can provide complementary information, which enhances the understanding of complex processes such as NM/NP delivery to the lung in a quantitative way on various scales (whole lung to cellular). The strengths and weaknesses of all five imaging modalities used here are summarized with respect to 2D/3D imaging capability, resolution, fidelity (conservation of original anatomical 3D structure), anatomical information, and technical complexity as summarized in Table .…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…PB‐PCXI utilizes differences in X‐ray refractive index and associated phase shifts at air–tissue interfaces for enhancing soft tissue contrast (e.g., in the lung) as compared to X‐ray absorption . Building on our previously published in vivo PB‐PCXI studies in murine lungs, the present study demonstrates that combined in vivo PB‐PCXI and ex vivo fluorescence imaging can provide complementary information, which enhances the understanding of complex processes such as NM/NP delivery to the lung in a quantitative way on various scales (whole lung to cellular). The strengths and weaknesses of all five imaging modalities used here are summarized with respect to 2D/3D imaging capability, resolution, fidelity (conservation of original anatomical 3D structure), anatomical information, and technical complexity as summarized in Table .…”
Section: Discussionmentioning
confidence: 62%
“…It is not intuitively clear how a bulk liquid injected into the trachea via intratracheal instillation can reach the deeper parts of the lung. In vivo PB‐PCXI revealed that the instilled bulk liquid is not primarily flowing down the bronchial tree, but is distributed quite uniformly throughout the lung by secondary aerosol formation due to occasional blockage of the airways with liquid and subsequent bursting of this blockage during breathing activity (Videos S1–S3, Supporting Information) . As mentioned above, the slow‐instillation process (24 s for 100 µL; 4.2 µL s −1 ), which was used here for the sake of in vivo PB‐PCXI imaging, is not identical to the typically used, rapid manual instillation (<1 s, >50 µL s −1 ).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations